Green Marketing Strategies for Local Community Empowerment Based on Halal Tourism - Ratna Dewi; Aryati Arfah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the implementation of green marketing strategies in local community empowerment based on halal tourism at Pantai Biru, Makassar. With the increasing demand for halal tourism, it is essential to integrate sustainability concepts in the development of tourism destinations. This research focuses on how green marketing strategies can strengthen local community empowerment while enhancing the attractiveness of halal tourism. The methodology used in this research is a quantitative approach with SWOT analysis, involving primary data collection through surveys and in-depth interviews with visitors and tourism managers. The study also employs validity and reliability techniques to ensure the quality of the collected data. The results indicate that the implementation of green marketing strategies can increase local community awareness of the importance of sustainability in managing tourism destinations. Furthermore, collaboration between the public sector, private enterprises, and local communities is key to the success of developing environmentally friendly halal tourism. The findings also indicate that green marketing strategies can enhance service and facility quality, thereby strengthening Pantai Biru's position as a sustainable halal tourism destination.